The Application of Whispering Chain Method in Chinese Listening Skills Practice of Junior High School Students in Makassar - Fahmi, Muhammad Khairul; R, Mantasiah; Junaeny, Arini (Journal of Maobi, 2024)
In the digital era increasing and developing, Mandarin is one of the languages widely used by the community in communication. Mandarin is an international language that ranks second after English. There are four aspects of competence in basic Chinese learning; listening 听力 (tīnglì), reading 阅读 (yuèdú) as receptive skills, and speaking 口语 (kǒuyǔ) writing 写作 (xiězuò) as productive skills. Based on the observations and interviews with Chinese language teachers at Frater Junior High School in Makassar seventh-grade students still lack listening skills. In response to these problems, it is necessary to learn about one of the interesting learning methods, which is called Chain Whispering. This article discusses the planning, process, and results of applying the chain whisper method in training students' listening skills. In line with the purpose of this study, to obtain data in the form of planning, process, and results from applying the chain whisper method in training students' listening skills. The type of research used is classroom action research. The findings of this study are that students' listening skills are trained with an average score of student learning outcomes in cycle I 83.21 increasing in cycle II to 89.64. Supported by teacher and student observation sheets that experienced positive changes from cycle I and cycle II.